Febrile rhabdomyolysis of unknown origin in refugees coming from West Africa through the Mediterranean. (September 2017) - Odolini, Silvia; Gobbi, Federico; Zammarchi, Lorenzo; Migliore, Simona; Mencarini, Paola; Vecchia, Marco; di Lauria, Nicoletta; Schivazappa, Simona; Sabatini, Tony; Chianura, Leonardo; Vanino, Elisa; Piacentini, Daniela; et al.
Highlights: Rhabdomyolysis is a complex medical condition involving the rapid breakdown of damaged skeletal muscle. An increasing number of cases of febrile rhabdomyolysis have been observed in migrants coming from West Africa via the sea. It was not possible to identify a specific aetiological diagnosis of the rhabdomyolysis. Genetic predisposing factors favouring clinical manifestations, unknown infections, or unreported non-conventional remedies may be involved. Targeted surveillance of rhabdomyolysis cases is warranted. Abstract: Objectives: Cases of undiagnosed severe febrile rhabdomyolysis in refugees coming from West Africa, mainly from Nigeria, has been observed since May 2014. The aim of this study was to describe this phenomenon. Methods: This was a multicentre retrospective observational study of cases of febrile rhabdomyolysis reported from May 2014 to December 2016 in 12 Italian centres. Results: A total of 48 cases were observed, mainly in young males. The mean time interval between the day of departure from Libya and symptom onset was 26.2 days. An average 8.3 further days elapsed before medical care was sought. All patients were hospitalized with fever and very intense muscle aches. Creatine phosphokinase, aspartate aminotransferase, and lactate dehydrogenase values were abnormal in all cases. The rhabdomyolysis was ascribed to an infective agent in 16 (33.3%) cases. In the remaining cases, the aetiology was undefined. Four out of seven patients tested had sickle cell trait. No alcohol abuse or drug intake was reported, apart from a single reported case of khat ingestion. Conclusions: The long incubation period does not support a mechanical cause of rhabdomyolysis. Furthermore, viral infections such as those caused by coxsackievirus are rarely associated with such a severe clinical presentation. It is hypothesized that other predisposing conditions like genetic factors, unknown infections, or unreported non-conventional remedies may be involved. Targeted surveillance of rhabdomyolysis cases is warranted.